2004
DOI: 10.1108/14637150410539696
|View full text |Cite
|
Sign up to set email alerts
|

How to configure cyber chains via competence networks

Abstract: Due to their common role as suppliers, small and medium‐sized enterprises (SMEs) are especially challenged by today's turbulent business conditions. In order to meet this challenge, short‐term Internet‐based enterprise co‐operations are regarded as an appropriate way to enhance the competitive strength of SMEs. Hence, the Institute of Machine Tools and Industrial Management (IWB) operates three so‐called competence networks for engineering (www.engineering‐net.de), rapid prototyping (www.rp‐net.de) and manufac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Technological investments would aid in the potential growth of SMEs beyond what was previously expected (Pratono, 2016). Further studies highlighted the role of short-term internet-based enterprise co-operations in improving an SME's competitive advantage (Berlak and Weber, 2004). SMEs need to enhance their competitive advantage through the use of technological investments and e-commerce solutions (Subba Rao et al, 2003;Papazafeiropoulou et al, 2002).…”
Section: Theories and Literature Reviewmentioning
confidence: 94%
“…Technological investments would aid in the potential growth of SMEs beyond what was previously expected (Pratono, 2016). Further studies highlighted the role of short-term internet-based enterprise co-operations in improving an SME's competitive advantage (Berlak and Weber, 2004). SMEs need to enhance their competitive advantage through the use of technological investments and e-commerce solutions (Subba Rao et al, 2003;Papazafeiropoulou et al, 2002).…”
Section: Theories and Literature Reviewmentioning
confidence: 94%
“…Business results and outcomes Blome et al (2013), Bowersox et al (2000), Chiadamrong and Suppakitjarak (2008), Ellinger et al (2011Ellinger et al ( , 2012, Essex et al (2016), Golini et al (2014), Hsu et al (2011), Ling-Yee andOgunmokun (2001), Shukla et al (2013) 10 Strategic management Ambulkar et al (2016), Armoutis et al (2008), Berlak and Weber (2004), Chikán and Gelei (2010), Drejer and Sørensen (2002), Ellinger et al (2015), Feldmann and Olhager (2013), Kusaba et al (2011), Lin et al (2016, Lutz and Ritter (2009), Mollenkopf and Dapiran ( 2005 found in the literature. We contend that a two-dimensional approach to literature content analysis allows us to address both the level of analysis and the elements of competence, and to create a foundation for further discussions about the interaction between the two.…”
Section: Research Stream Publication References Countmentioning
confidence: 99%
“…Functional Armoutis et al (2008), Barclay (2005), Barnes and Liao (2012), Berlak and Weber (2004), Bernon and Mena (2013), Blome et al (2013), Bowersox et al (2000), Bölsche et al (2013), Chiadamrong and Suppakitjarak (2008), Chikán and Gelei (2010), Cox (2001), Das and Narasimhan (2000), Davis and Golicic (2010) 2010), Richey and Wheeler (2004), Rosenzweig andRoth (2007), Sangari. andRazmi (2015), Schoenherr et al (2014), Shou and Wang (2015), Shukla et al (2013), Sohal (2013, Spekman et al (2002), Sun (2013), Thai (2012a,b), Thai and Yeo (2015), Tokman et al (2011), Torkkeli (2014, Wadhwa et al (2008), Varella.…”
Section: Elements Of Competence Publication References Countmentioning
confidence: 99%
“…True Heterarchical Form requires that a manufacturing system has no overall supervisor, with entities selfconfiguring in the achievement of manufacturing. It is noted that in the context of Additive Manufacturing, a similar notion was proposed by Berlak and Webber 53 in 'competence networks'; however, in this system, a definite controller coordinates the product fulfilment process.…”
Section: Heterarchical Form: Mfr C Joint Venturementioning
confidence: 76%